Impact of clinical parameters and vascular haemodynamics on arterio-venous fistula maturation in patients with end stage renal disease: A prospective study on Indian patients. Issue 4 (July 2022) - Ghosh, Nalini Kanta; Bhattacharjee, Hemanga Kumar; Prajapati, Omprakash; Krishna, Asuri; Kumar, Atin; Mahajan, Sandeep; Bansal, Virinder Kumar
Background: About 18%–65% of Arterio-Venous fistula (AVF) made to facilitate haemodialysis in end stage renal disease patient fail to mature. This study was designed to evaluate the impact of clinical parameters and vascular haemodynamics on maturation of AVF on Indian patients. Material and methods: This was a prospective observational study. Eligible patients' clinical profiles and vascular haemodynamics by Doppler ultrasonography were noted. All patients underwent radio-cephalic AVF on the non-dominant arm under local anaesthesia. Clinical definition was used to assess success rate of AVFs which is defined as successful six settings of satisfactory dialysis. Data were analysed using Stata/12.0 software. Independent t -test, chi-square test, logistic regression analysis and multivariate analysis were used. The p -value of <0.05 was considered significant. Results: A total of 205 patients were enrolled and analysed. Among clinical factors, age, sex, serum creatinine, hypertension had no significant association with failure (p = 0.5, 0.08, 0.76 and 0.74). Patient's BMI and presence of diabetes had significant impact on outcome ( p < 0.001 and 0.02 respectively). Among vascular haemodynamics, radial vein diameter of >2.5 mm and radial artery flow rate >40 ml/min had no significant association with failure ( p = 0.12 and 0.28). Diameter of radial artery (>2 mm) and intra-operatively immediate thrill were independent predictor of success (p = 0.002 and <0.001). Conclusion: In the present study rate of fistula, maturation was 73.2% without any post-operative radiological intervention. Radial artery diameter >2 mm and presence of immediate thrill post-operatively were significantly associated with successful cannulation.